Depreciation Systems in Nepal: A Comparison Based on ETR - Kandel, Puspa Raj (NRB Economic Review, 2003)
The administrator after the introduction of Income Tax Act, 2002 has claimed that the depreciation rule under the new law is more generous than the depreciation rule of 1992 in case of all the assets including machinery and building. The analysis made on the basis of ETR, however, shows no decrease in ETRs in 2002 in comparison to 1992. That means, the depreciation rule of 2002 in case of building and machinery is not generous as claimed by the tax policy maker. In opposite of this, the analysis proves that the depreciation provisions of 1992 and 2002 are more liberal than the depreciation provisions of earlier periods.